Structure extraction and keyword-based filtering for applying Malik Bennabi’s ruler on intellectual property of Islamic finance and banking - Othman, Roslina; Noordin, Mohamad Fauzan; Gustama, Ria Hari; Zulkifli, Zahidah; Tengku Sembok, Tengku Mohd (2016)
This paper presents our work in structure extraction and keyword-based filtering for implementing Malik Bennabi’s ruler on Intellectual Property (IP) of Islamic Finance and Banking. These two processes are the first two parts in the architecture of the system after retrieving the data. We applied Malik Bennabi’s thoughts as the benchmark in measuring process and used journal articles as one of IP form as the data to be processed in the ruler. Structure extraction is aimed at providing the most important structure of the article so that they can be measured by the ruler to identify whether the article’s content is in line with Malik Bennabi’s thought. We extracted abstract and keywords parts of the article as they represent the entire information in the article. In order to have an efficient measurement process, we did filtering on the articles to distinguish those that derived Malik Bennabi’s thought from ones that do not. This filtering was done by checking the article keywords whether they exist in the list of keywords derived from Malik Bennabi’s articles (MB keywords). Surprisingly, structure extraction results show that not all articles have the keywords. It was shown there were only 66.92 % papers came with keywords inside. Meanwhile, results in keyword-based filtering process delivered a worse performance where there were only 2.26 % articles filtered on MB keywords.